2010
DOI: 10.1172/jci43029
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin receptor 1A–modulated phosphorylation of glycine receptor α3 controls breathing in mice

Abstract: Rhythmic breathing movements originate from a dispersed neuronal network in the medulla and pons. Here, we demonstrate that rhythmic activity of this respiratory network is affected by the phosphorylation status of the inhibitory glycine receptor α3 subtype (GlyRα3), which controls glutamatergic and glycinergic neuronal discharges, subject to serotonergic modulation. Serotonin receptor type 1A-specific (5-HTR 1A -specific) modulation directly induced dephosphorylation of GlyRα3 receptors, which augmented inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 46 publications
4
92
0
4
Order By: Relevance
“…They are also found in Botzinger complex, Pre-Botzinger complex, and spinal trigeminal nucleus in the brainstem where they appear to control rhythmic activity of respiratory networks (Manzke et al, 2010). Overall, our data support the conclusion that GlyRs containing a3 in these locations are relatively insensitive to ethanol and Gbg modulation.…”
Section: Effect Of Glyr A3 Splicing and C Terminus On Ethanol Sensitisupporting
confidence: 82%
See 1 more Smart Citation
“…They are also found in Botzinger complex, Pre-Botzinger complex, and spinal trigeminal nucleus in the brainstem where they appear to control rhythmic activity of respiratory networks (Manzke et al, 2010). Overall, our data support the conclusion that GlyRs containing a3 in these locations are relatively insensitive to ethanol and Gbg modulation.…”
Section: Effect Of Glyr A3 Splicing and C Terminus On Ethanol Sensitisupporting
confidence: 82%
“…Furthermore, it is also unknown whether this GlyR subtype is modulated by Gbg. This subunit has clinical significance because it is involved in the control of rhythmic breathing (Manzke et al, 2010), and ethanol modulation of this GlyR subtype could be responsible for the respiratory depression induced by excessive alcohol consumption. In addition, modulation of a3 GlyRs by Gbg through the activation of G protein-coupled receptors could be relevant for the regulation of glycinergic inhibition in other physiologic processes, such as central pain sensitization (Harvey et al, 2004;Manzke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential explanation for these differences is that defective presynaptic glycine uptake is predicted to affect the function of multiple GlyR subtypes, i.e., ␣2␤ and ␣3␤, as well as the predominant ␣1␤ isoform. In this regard, it is noteworthy that GlyR ␣3 knock-out mice were recently shown to have an irregular respiratory rhythm (45).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that systemic 5-HT 1A R agonists can reverse the apneustic disturbances (i.e., pronounced prolongation of inspiratory duration) resulting from a variety of respiratory defects in patients and animal models (Wilken et al 1997), presumably via 5-HT 1A R-mediated enhancement of glycinergic inhibition in brainstem respiratory networks (Manzke et al 2009(Manzke et al , 2010. Consistent with this view, we found that microinjection of the specific NMDA (NMethyl-D-aspartate) receptor antagonist AP5 (20 mM) into the KFN unilaterally induced an apneustic pattern ( Fig.…”
Section: Distinct Spinal/supraspinal 5-ht 1a R Modulation Of Respirationmentioning
confidence: 99%